2018
DOI: 10.1111/ipd.12415
|View full text |Cite
|
Sign up to set email alerts
|

Use of stainless steel crowns to restore primary molars in Germany: Questionnaire‐based cross‐sectional analysis

Abstract: Independent of the technique used, SSCs are considerably underutilized in the dental practice in Germany, although SSCs are well accepted by the universities, however, predominantly using the conventional approach.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
23
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(29 citation statements)
references
References 32 publications
(97 reference statements)
3
23
3
Order By: Relevance
“…The perceived technique complexity also appeared to be associated with practitioners' reluctance to use PMCs, with 28.9% of the respondents believing that it was one of the obstacles to implementing the PMCs technique. 14 In the present study, however, only 9.3% of respondents thought so. The low economic bene t was reported as the second leading limitation to the use of PMCs in the present study, with 14.9% of respondents believing that it was a reason for their reluctance to apply this technique.…”
Section: Discussioncontrasting
confidence: 75%
See 2 more Smart Citations
“…The perceived technique complexity also appeared to be associated with practitioners' reluctance to use PMCs, with 28.9% of the respondents believing that it was one of the obstacles to implementing the PMCs technique. 14 In the present study, however, only 9.3% of respondents thought so. The low economic bene t was reported as the second leading limitation to the use of PMCs in the present study, with 14.9% of respondents believing that it was a reason for their reluctance to apply this technique.…”
Section: Discussioncontrasting
confidence: 75%
“…The results showed that approximately one-third of the respondents (30.4%) used PMCs to restore the defects in primary molars in their clinical practice, consistent with the results of previous studies in Germany and the UK. 14,15 In the study conducted in Germany, general and paediatric dentists were investigated, and only 34% of the respondents routinely used the PMCs technique. Additionally, in the study conducted in the UK, 3% of the participants routinely used PMCs, with 15% infrequently, and 82%…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…7 Stainless steel crowns are still underutilized in various countries, and many of the dental surgeons are not familiar with the HT. 11 HT has been found to be durable and economical treatment option for treating carious primary molars. HT is preferred over more invasive treatment options but requires proper case selection and pulpal status diagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…Traditional SSCs allow dentists to trim, crimp, and shape in order to better adapt to the cervical portion of the primary teeth. Santamaría et al [9], in their questionnaire-based study in Germany, reported that dentists generally find SSCs to be technically complex, esthetically displeasing…”
Section: Introductionmentioning
confidence: 99%